Towards the definition of an information quality metric for information fusion models. (January 2021) - Paggi, Horacio; Soriano, Javier; Lara, Juan A.; Damiani, Ernesto
Highlights: Managing Information quality (IQ) is a key issue in distributed scenarios. Little research has been conducted regarding the definition of IQ metrics. We present a novel IQ metric that can be used in information fusion models. The results obtained in the performance of the model confirm the validity of the IQ metric. Abstract: Managing information quality has become important in cyber-physical systems dealing with big data. In this regard, different models have been proposed, mainly in flat peer-to-peer networks, in which exchanging information efficiently is a key aspect due to scarce resources. However, little research has been conducted on information quality metrics for cyber-physical scenarios. In this paper, we propose an information quality metric and show its application to an information fusion model. It is a "model-oriented quality metric" since it allows non-predefined variants on its configuration depending on the application domain. The model was tested on several simulations using open datasets. The results obtained in the performance of the model confirm the validity of the information quality metric, proposed in this paper, on which the model is based. The model may have a wide variety of applications such as mobile recommendation or decision making in critical environments (emergencies, war, and so on). Graphical abstract: Image, graphical abstract